Studies in East Asian economies : capital flows, exchange rates, and monetary policy - Handa, Jagdish; Kahsay, Shibeshi Ghebre (World Scientific, 2011)
"This book presents five theoretical and empirical studies on growth, capital flows, exchange rates and monetary policy. The empirical parts of three of the studies use data from the ASEAN-4 countries of Indonesia, Malaysia, Philippines, Thailand, with the remaining two studies using data on China."--Preface.